2004
DOI: 10.1103/physrevb.69.094201
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic structure of Fe-Ni and Fe-Ni-S molten alloys of geophysical interest

Abstract: 0.15 . From data at hand no clear evidence of the clustering of sulfur within the Fe-Ni matrix is found. In contrast, the addition of sulfur leads to significant changes in structural and some dynamical properties that can be inferred from knowledge of the static structure factors. Such dynamical changes seem to arise as a result of a strong decrease of the elastic moduli of the alloys resulting from interactions with a light element rather than from a density effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Cuello et al . [] showed that adding sulfur to liquid Fe‐Ni alloys yielded a less packed structure that departs further from the bcc ‐like structure of the pure liquid Fe‐Ni alloy at ambient pressure. Furthermore, high‐pressure structural studies have shown that the liquid Fe‐S alloy structure of less than 6 GPa is poorly organized beyond roughly 5–6 Å, that is, much less intermediate‐ and long‐range ordering [ Urakawa et al ., ; Sanloup et al ., ; Morard et al ., ; Kono et al ., ].…”
Section: Discussion and Geophysical Implicationsmentioning
confidence: 99%
“…Cuello et al . [] showed that adding sulfur to liquid Fe‐Ni alloys yielded a less packed structure that departs further from the bcc ‐like structure of the pure liquid Fe‐Ni alloy at ambient pressure. Furthermore, high‐pressure structural studies have shown that the liquid Fe‐S alloy structure of less than 6 GPa is poorly organized beyond roughly 5–6 Å, that is, much less intermediate‐ and long‐range ordering [ Urakawa et al ., ; Sanloup et al ., ; Morard et al ., ; Kono et al ., ].…”
Section: Discussion and Geophysical Implicationsmentioning
confidence: 99%
“…In this case, we have carried out total structure factor determinations for three different alloys (two FeNi and one FeNiS, Fig. 1) in order to determine whether FeS clusters are present in these alloys or not [7]. The presence of this kind of clusters could explain the observed anomalies in the sound propagation.…”
Section: Diffractometersmentioning
confidence: 94%
“…Pair distribution functions g(r) for the three alloys taken from Ref. [7]. The inset depicts the corresponding pair correlation functions, D(r) = 4pr[g(r) À 1] (same symbols).…”
Section: Triple Axes Spectrometersmentioning
confidence: 99%
“…A preliminary report on the structure of such alloys has already appeared [8], as well as an experimental study on the collective dynamics of liquid Ni [9]. There, some peculiarities of the observed excitation parameters with respect to those exhibited by molten alkali metals [10], such as an apparent lack of strong deviation from hydrodynamic sound with increasing wavevector, were evidenced.…”
Section: Introductionmentioning
confidence: 90%